2019
DOI: 10.18785/jetde.1201.03
|View full text |Cite
|
Sign up to set email alerts
|

Social Media in Dynamic Learning: Logistics and Influential Factors

Abstract: Educators have been using social media to enrich learning activities and promote interactive and collaborative learning. Under the context of dynamic learning-the way that 21st century's learners learn, the new challenges are: how educators design such a setting to effectively integrate certain social media tools to improve learning, and what the influential factors might be that educators need to focus during the design. In this article, we employ the concept "logistics" to explain and redefine dynamic design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Second, this study was only able to retain 67 cases in the final sample due to strict inclusion criteria. For an expected odds ratio to be 3.0, a sample size of 96 is needed for logistic regression analysis (Liu et al, 2019). The comparatively small sample size may limit the generalizability of the study.…”
Section: Limitationsmentioning
confidence: 99%
“…Second, this study was only able to retain 67 cases in the final sample due to strict inclusion criteria. For an expected odds ratio to be 3.0, a sample size of 96 is needed for logistic regression analysis (Liu et al, 2019). The comparatively small sample size may limit the generalizability of the study.…”
Section: Limitationsmentioning
confidence: 99%
“…In addition, an experiment conducted by Lu and Wang (2019) using an AI-powered English learning platform demonstrated that using AI in language learning could improve students' motivation, engagement, and satisfaction. The study found that students using the platform had higher motivation and engagement levels than those without and reported higher satisfaction with the learning experience.…”
Section: Benefitsmentioning
confidence: 99%
“…With ADDIE integrated in all three dimensions, the ITD model has been tested to be effective over years from a series of case analysis, for example, on the following themes: (a) using Web 2.0 in teacher education with 88 published cases (Liu & Maddux, 2008), (b) the effectiveness of flipped learning with 216 published cases (Liu, Ripley, & Lee, 2016), (c) technology and dynamic design in counseling education and practice with 261 published cases (Liu, Li, & Shcherer, 2016), and (d) social media in dynamic learning with 276 cases (Liu, Chen, & Li, 2019). Those case analyses were performed with logistic 109 regressions, and the results consistently demonstrated that all three dimensions integrated together was the necessary and sufficient condition leading to the expected learning outcomes.…”
Section: Integration Design and Instructional Design: What Is True?mentioning
confidence: 99%